A Study on the Instruments Preferred by Key Stakeholders to Promote Organic Fertilizer through Agri-Food Value Chains - Jayakodi, J.A.S.N.S.; Jayasinghe-Mudalige, U.K.; Jayathilake, H.A.C.K. (University of Jaffna, 2020)
Consumption of organic food and agricultural products have been expanded remarkably in the recent past and the terms like ‘organic agriculture / products’, in general, and ‘organic fertilizer’ that in particularly in use to demarcate one of the key inputs utilized in such systems become increasingly popular. On the understanding that positive changes to the perceptions of stakeholders along the agri-food values chains generate such trends and a mindset, this study was focused on investigating the promotional instruments of organic fertilizer preferred by key stakeholders in specifically fruits and vegetables production value chain in Sri Lanka. Multiple approaches was operated to gather both primary and secondary data by way of Review of Literature, Focus Group Discussions and Key-Informant Interviews where a structured questionnaire based personal interview-oriented stakeholder survey was carried out with over 140 individuals attached to organic fertilizer oriented agri-food value chains. The responses of whom were captured by setting a set of objective statements and each respondent was directed to score on them using 10-point likert-scale. The values provided on this scale were subjected to Exploratory Factor Analysis techniques to test for their ‘validity’ and ‘reliability’ and the outcome was used to derive Mean Attitude Score (MAS). Exploratory Factor Analysis shows that those instruments can be catalogued objectively under four attributes, termed as: ‘Self’, ‘Market’, ‘Government’ and ‘Judiciary’. The outcome of Kruskal Wallis test revealed that at least those preferences of one stakeholder type is different from others. The outcome of the whole study provides insights as to how an appropriate policy environment with right instruments can be formulated to promote organic agriculture, where the majority of stakeholders highly preferred ‘Government Intervention’ to regulate followed by other institutions to facilitate such efforts.
Keywords: Agri-food value chain; Organic fertilizer; Promotional instruments; Stakeholder preferences